Corticotropin-releasing factor depolarizes rat lateral vestibular nuclear neurons through activation of CRF receptors 1 and 2. (August 2019) - Wang, Yi; Chen, Zhang-Peng; Yang, Zhong-Qin; Zhang, Xiao-Yang; Li, Jian-Mei; Wang, Jian-Jun; Zhu, Jing-Ning
Abstract: Corticotropin-releasing factor (CRF) is a neuropeptide mainly synthesized in the hypothalamic paraventricular nucleus and has been traditionally implicated in stress and anxiety. Intriguingly, genetic or pharmacological manipulation of CRF receptors affects locomotor activity as well as motor coordination and balance in rodents, suggesting an active involvement of the central CRFergic system in motor control. Yet little is known about the exact role of CRF in central motor structures and the underlying mechanisms. Therefore, in the present study, we focused on the effect of CRF on the lateral vestibular nucleus (LVN) in the brainstem vestibular nuclear complex, an important center directly contributing to adjustment of muscle tone for both postural maintenance and the alternative change from the extensor to the flexor phase during locomotion. The results show that CRF depolarizes and increases the firing rate of neurons in the LVN. Tetrodotoxin does not block the CRF-induced depolarization and inward current on LVN neurons, suggesting a direct postsynaptic action of the neuropeptide. The CRF-induced depolarization on LVN neurons was partly blocked by antalarmin or antisauvagine-30, selective antagonists for CRF receptors 1 (CRFR1) and 2 (CRFR2), respectively. Furthermore, combined application of antalarmin and antisauvagine-30 totally abolished the CRF-induced depolarization. Immunofluorescence results show that CRFR1 and CRFR2 are co-localized in the rat LVN. These results demonstrate that CRF excites the LVN neurons by co-activation of both CRFR1 and CRFR2, suggesting that via the direct modulation on the LVN, the central CRFergic system may actively participate in the central vestibular-mediated postural and motor control. Highlights: CRF depolarizes both spontaneous firing and silent neurons in the LVN. CRF-induced excitation on LVN neurons is a direct postsynaptic effect. CRFR1 and CRFR2 co-mediate the excitation induced by CRF on LVN neurons. CRFR1 and CRFR2 are co-localized on the same LVN large neurons.